PERANAN TANAMAN PAKAN DALAM PELESTARIAN LINGKUNGAN DI INDONESIA (Dengan Perhatian Khusus pada Konservasi Tanah) - B.R. Prawiradiputra (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Environmental friendly agriculture needs technology application which is adaptable to environment. Among other is application of soil conservation. However the research on integration of forages in soil conservation is conducted about last 30 years. Yet, not all of research results are adopted by farmers; there are lots of problems in application. The paper present research results of forages as soil conservation crops, especially in upper watershed which is done at many places for about more than 25 years. The outline of the paper is not based on time or region of works but more on the methods applied. The methods of soil conservation are (a) planting of forages on terraced sloping land, (b) grass strip, (c) three strata system, (d) cover crops and (e) alley cropping. On the other hand the problems of forages as soil conservation crops are also presented, (a) lack of socialize of the importance of forages and (b) unfamiliar of very good cover crops businesses.